Electrification pathways for U.S. passenger vehicles - Matteo Muratori; Catherine Ledna; Paige Jadun; Chris Hoehne; Arthur Yip; Kara Podkaminer (npj Sustainable Mobility and Transport)
Abstract As electric vehicle (EV) adoption continues to accelerate, we explore the implications of different adoption trajectories that achieve a full transition to EVs by 2050 for U.S. light-duty passenger vehicles (LDVs). Using a vetted transportation system model, we find that achieving 100% EV sales by 2040 would decrease tailpipe greenhouse gases (GHGs) by 90% between 2022 and 2050, leaving about 45 million gasoline vehicles on the road. Achieving 100% sales by 2035, tailpipe emissions decrease 93%, with about 28 million gasoline vehicles on the road in 2050 (9% of stock). Slower EV adoption, reaching 100% sales by 2045, would result in 69 million gasoline vehicles on the road in 2050. Fully electrifying passenger vehicles by 2050 would require a full transition to EVs sales in the 2030s coupled with either changes to mobility, or an accelerated stock turnover in the 2040s with additional 19–30% annual LDV sales.